Working conditions, grievance procedures and fringe benefits as determinants of labour turnover in selected industries in Oyo state, Nigeria (2014)
"Many factors are responsible for labour turnover in work organisations ranging from long working hours, violence at work, low wages and income; poor working conditions, grievance procedures, lack of motivation and job satisfaction to inadequate fringe benefits with resultant effects such as low productivity, increase in cost of production, reduction in number of personnel, and so on. It is against this background that this study employs the descriptive survey research design of the ex post facto type to find out the relationship among working condition, grievance procedure, fringe benefit and labour turnover. The population for the study consists of members of labour union and management in selected industries which are basically manufacturing. The Multistage sampling technique was used to select three hundred and ten respondents. The main instrument used to elicit information from respondents is a questionnaire tagged 'Working Condition, Grievance Procedure, Fringe Benefit and Labour Turnover Questionnaire - WCGPFBLTQ with four sub sections. Two hundred and eighty-eight questionnaires were recovered and found usable for the research. Pearson Product Moment Correlation was used to test the research hypotheses at 5% level of significance. The findings show that there were positive significant relationships among working condition, grievance procedures, fringe benefits and labour turnover. The study recommends that the management team of the workplace should formulate, implement and adhere to good policies on working conditions, grievance procedure and fringe benefits within their establishments. These decisions will increase productivity, reduce absenteeism, increase job satisfaction and wellbeing of employees. "